Risk Mitigation Strategies for Rice Marketing in Kendari City - Erin Kristina; Weka Gusmiarty Abdullah; Ilma Sarimustaqiyma Rianse (International Journal of Technology and Education Research, 2024)
This study aims to analyze price risk in rice marketing and to analyze mitigation strategies for rice price risk in Kendari City. The research area was determined purposively based on the consideration that the location is closer to where I live. Respondents consisted of 25 people. Data analysis using Fuzzy FMEA analysis. The results showed that there are five sources of price risk in rice marketing. Namely, delays in product production, market demand that occurs if market demand does not match the stock of rice produced, increases in grain prices, large stocks of products that have not been sold out and then experience rising prices due to harvest season increases and, products sold have similar competing products. This research also shows that the mitigation strategy for each source of price risk in rice marketing is routine and scheduled machine maintenance, making supplies that allow the Company to meet demand, product promotion, finding new markets, and expanding the distribution of customer service quality, and utilizing social media to interact with customers